PELATIHAN PEMBUKUAN SEDERHANA DAN MENGGUNAKAN APLIKASI SIAPIK PADA UMKM DESA LANCANG KUNING - Yanto, Meidi; Irawan, Adi Chandra; Rahmayani, Desrika; Yulianrie, Errin; Putra, Guntur Leo; Meisya, Meisya (P3M STIE Pembangunan Tanjungpinang, 2025)
This research discusses the challenges faced by micro, small and medium enterprises (MSMEs) in Kunning Village, Lancang Harbor regarding recording financial transaction reports. A survey of economic stakeholders in MSMEs revealed that the problem is that it is still difficult for economic stakeholders in MSMEs to understand manual recording such as reporting income, expenses and budget planning. This initiative aims to provide training on the operation of the Android or iOS-based SiApik application issued by Bank Indonesia to record financial reporting transactions, as well as basic accounting manual training. Social service activities are carried out through consultation, training and guidance, especially to overcome the problems faced by MSMEs in Lancang Cangning Village. This activity was carried out to provide MSMEs with an understanding of basic financial and accounting reporting and to provide practical examples of the application of these training concepts. Kuala Lobam. Apart from that, the benefits of this activity can increase strong awareness of the importance of entrepreneurship starting from a young age. In the formation of the soul entrepreneur The students of SMKN 1 Seri Kuala Lobam are given education by providing motivation to improve the formation of the soul entrepreneur.